2013
DOI: 10.1007/s10943-013-9755-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress and World Assumptions: The Effects of Religious Coping

Abstract: Religiosity has been shown to moderate the negative effects of traumatic event experiences. The current study was designed to examine the relationship between post-traumatic stress (PTS) following traumatic event exposure; world assumptions defined as basic cognitive schemas regarding the world; and self and religious coping conceptualized as drawing on religious beliefs and practices for understanding and dealing with life stressors. This study examined 777 Israeli undergraduate students who completed several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…In this case, we observed that subjective severity influenced the increase of PTS only when negative RC is medium or high. These results show that religiosity does serve a moderating role between predictive variables and psychological responses after stressing events, which has been found in other studies [30,32,33], strengthening the negative impact of subjective severity when it is high. However, as Harris et al [15] suggested, severity and Time 1 PTS could predict negative RC and this form of coping could act as a mediational path between baseline traumatic reactions and Time 2 PTS.…”
Section: Discussionsupporting
confidence: 84%
“…In this case, we observed that subjective severity influenced the increase of PTS only when negative RC is medium or high. These results show that religiosity does serve a moderating role between predictive variables and psychological responses after stressing events, which has been found in other studies [30,32,33], strengthening the negative impact of subjective severity when it is high. However, as Harris et al [15] suggested, severity and Time 1 PTS could predict negative RC and this form of coping could act as a mediational path between baseline traumatic reactions and Time 2 PTS.…”
Section: Discussionsupporting
confidence: 84%
“…Zukerman et al () reported that nonreligious participants actually demonstrated higher levels of negative religious coping and intrapersonal religious coping. Relatively high levels of negative religious coping were also found among nonreligious participants in Zukerman and Korn (). In Kucharska (), a “God concept” construct was used, comprising dimensions such as benevolent, forgiving, severe and distant God.…”
Section: Resultsmentioning
confidence: 84%
“…One conceptual issue associated with religious coping is religious appraisals/meaning‐making. In Zukerman and Korn (), positive religious coping was associated with general world assumptions following trauma. Negative religious appraisals of an event (i.e., the notion of being punished by God) was associated with the severity of symptoms of mental disorders in Berzengi et al (), Blanc, Rahill, Laconi, and Mouchenik (), Feder et al (), Sezgin & Punamäki, (, although the “human” appraisals were associated with even more severe psychopathology), and Rosellini et al ().…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies of basic assumptions have demonstrated that deviation from mean values is more typical of situations that are rare in people's lives (for example, high levels of stress and PTSD, high level of anxiety. Our results demonstrate that students have normal beliefs without negative symptoms (Zukerman & Korn, 2014;Grills-Taquechel, Littleton, & Axsom, 2011;Ter Heide, Sleijpen, & Niels, 2017).…”
Section: Basic Assumptions Resultsmentioning
confidence: 50%